Islamic Education Methodology in the Context of Traditional and Modern Pesantren: A Historical Review of Education in Pesantren - Umam, M. Khotibul; Safuri, B.; Kultsum, Umi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
The purpose of this study is to explain and analyze the methodology of Islamic education in traditional boarding schools and contemporary pesantrens with a historical overview of pesantrens. As an Islamic educational institution, pesantren play a strategic role in shaping the personalities and understanding of the community. Using a qualitative approach, data was collected through a literature search and observation of educational practices in several boarding schools in Banten. The results showed that traditional boarding schools introduced the methods of Sulugun, Bandungangan, and Witnan. Meanwhile, the modern pesantrens applies the integration of the classical system, religious and general curricula, and the use of discussion, presentation, and technology methods. There are differences between these approaches, but both are of Sentri formation that have the same goal: Strong morals and strong Islamic insight. The study concluded that the integration of traditional values and modern approaches was an effective strategy in answering Banten's challenges regarding contemporary Islamic education.